Catch them young: Prevention with focus on vocational, e-learning, and self-sustainability among Asaba and Warri youths - Ulo, Edafe; Ejirefe, Influence (Journal of Interdisciplinary Studies in Education, 2026)
The study examined education toward crime prevention with the understanding that juvenile delinquency is a social problem that affects both developed and developing countries. The work adopted quantitative and qualitative approaches to explore educational approaches (vocational, e-learning, and self-sustainability) that are geared toward crime prevention among youth in Nigeria. The target population was youth aged 18 to 35 years in Asaba and Warri. A sample size of 250 respondents was drawn from cities. A total of 500 copies of questionnaires were administered; however, 482 (96.4%) were returned as valid. The findings indicated that vocational education improves access to market-relevant skills, economic participation, and crime prevention.